Hands-on simulation modeling with Python develop simulation models to get accurate results and enhance decision-making processes - Ciaburro, Giuseppe (Packt Publishing, 2020)
Developers working with the simulation models will be able to put their knowledge to work with this practical guide. You will work with real-world data to uncover various patterns used in complex systems using Python. The book provides a hands-on approach to implementation and associated methodologies to improve or optimize systems.